A novel GCMS method for the quantitative analysis of sodium oleate in froth flotation. (January 2022) - Gao, Ya; Fu, Xinzhuang; Yue, Tong; Sun, Wei
Highlights: A novel method of GCMS was proposed to quantitatively determine NaOL content in the flotation pulp. Compared with TOC and HPLC methods, GCMS can avoid systematical and manual operation error effectively. The methyl esterification pretreatment is required before NaOL samples are measured by GCMS. Better precision and stability can be obtained for GCMS due to the combination of external and internal standards in the fitting equation. Abstract: Sodium oleate (NaOL), as an important collector, has been extensively applied in oxide and silicate mineral flotation. The quantitative determination has to be analyzed for investigating its adsorption mechanism on the mineral surface. In this study, a novel method of Gas Chromatography Mass Spectrometry (GCMS) was proposed to precisely and stably measure NaOL concentration in diaspore and kaolinite flotation pulp through methyl esterification pretreatment. Compared with Total Organic Carbon (TOC) analyzer and High Performance Liquid Chromatography (HPLC), this method can avoid systematical and manual operation error effectively, benefitting from the internal standard application of heptadecanoic acid. The obtained linear relevance coefficient is 0.99902 and the standard deviation of adsorption results on the diaspore and kaolinite is much smaller than that of TOC and HPLC.